A substructure shaking table test for reproduction of earthquake responses of high-rise buildings. - Ji, Xiaodong (Earthquake engineering & structural dynamics.)
When subjected to long-period ground motions, high-rise buildings' upper floors undergo large responses. Furniture and nonstructural components are susceptible to significant damage in such events. This paper proposes a full-scale substructure shaking table test to reproduce large floor responses of high-rise buildings. The response at the top floor of a virtual 30-story building model subjected to a synthesized long-period ground motion is taken as a target wave for reproduction. Since a shaking table has difficulties in directly reproducing such large responses due to various capacity limitations, a rubber-and-mass system is proposed to amplify the table motion. To achieve an accurate reproduction of the floor responses, a control algorithm called the open-loop inverse dynamics compensation via simulation (IDCS) algorithm is used to generate a special input wave for the shaking table. To implement the IDCS algorithm, the model matching method and the H∞ method are adopted to construct the controller. A numerical example is presented to illustrate the open-loop IDCS algorithm and compare the performance of different methods of controller design. A series of full-scale substructure shaking table tests are conducted in E-Defense to verify the effectiveness of the proposed method and examine the seismic behavior of furniture. The test results demonstrate that the rubber-and-mass system is capable of amplifying the table motion by a factor of about 3.5 for the maximum velocity and displacement, and the substructure shaking table test can reproduce the large floor responses for a few minutes.